About some Indonesian Pachyrhynchus Germar 1824 with description of a new species (Coleoptera, Curculionidae, Entiminae, Pachyrhynchini) - Bollino, Maurizio (Zootaxa, 2023)
Pachyrhynchus faisali Bollino, sp. nov. is described from Teminabuan, West Papua, Indonesia. Pachyrhynchus forsteni Snellen van Vollenhoven is reported for the first time from Morotai Island and a second specimen of Pachyrhynchus viridis (Chevrolat) from Manokwari district is illustrated. In addition, the endophallus of three species of Papuan Pachyrhynchus and one Pantorhytes are illustrated.